ANALISIS PROFITABILITAS DAN LIKUIDITAS UNTUK MENILAI KINERJA KEUANGAN SELAMA MASA PANDEMI COVID-19 - khairunnisa khairunnisa; Hendra Harmain; Juliana Nasution (JURNAL ILMIAH MAHASISWA EKONOMI ISLAM, 2023)
The presence of the COVID-19 Virus, a deadly virus, shocked the majority of nations at the end of 2019. The company's performance, including its profit share, is unquestionably impacted by this condition, particularly in the pharmaceutical sector. Through liquidity and profitability ratios, the purpose of this study is to ascertain the financial performance of the company. A quantitative-descriptive method of research is used. The analysis of the data reveals that the profitability ratio, as measured by the average Return on Assets and Return on Equity from 2017 to 2021, respectively 0.5% and 1.64 percent, is below the industry average, and the liquidity ratio, as measured by the average Current Ratio from 2017 to 2021, is below the industry average. In contrast, the ratio of inventory to net working capital for 2017- 2021 has a negative result of -1,363%, which indicates that the ratio is not favorable due to the fact that current assets outnumber current liabilities. This demonstrates that the Covid-19 virus has a significant impact on the financial performance of the business. Suggestions from the author ensure that management always pays attention to the formal liquidity level set by the standards of the Ministry of BUMN